Noonan syndrome: A case report - Asokan S; Muthu M; Rathna Prabhu V (Wolters Kluwer Medknow Publications, 2007)
Noonan syndrome is a developmental disorder characterized by facial dysmorphia, short stature, cardiac defects and skeletal malformations. It may be sporadic or inherited as an autosomal dominant or recessive trait and occurs, one in 1000-2500 children. This is a case report of a 13 year-old girl who was referred by a general dental practitioner to a pediatric dentist for management. Full mouth dental rehabilitation was done and the child was brought to a dental institution for correction of orofacial and occlusal defects. Multidisciplinary treatment is the key to success in managing children with Noonan syndrome and the pediatric dentists play an important position to lead the health team.